GAYA PENGURUSAN KONFLIK GURU BESAR (Sains Humanika, 2008)
Conflict is a natural phenomenon faced by every individual in their communication process and interaction with others. Every individual has his/her own way of dealing with conflicts. In this research, consisted of five conflict management styles which were adapted from Thomas–Kilmann Model i.e competitive conflict management, accommodation, tolerance, collaboration and eluding were assessed. Respondents from this study were 88 head teachers from primary schools in Johor Bahru district. Two main statistics were used which descriptive statistics while inferential statistics were also being in testing the hypotheses. Descriptive analyses indicated that collaboration style was the most popular whereas competitive style was the least popular. The result of hypotheses testing indicated that there were no significant differences between sex, age, marital status, academic educational level and length of service as head of school and with conflict management styles among the heads of primary school studied.
Keywords: Head teachers; conflict management; collaboration style; accommodation style; competitive style